Jeremy Fink and the meaning of life - Mass, Wendy, 1967- (Little, Brown, 2008)
Just before his thirteenth birthday, Jeremy Fink receives a keyless locked box--set aside by his father before his death five years earlier--that purportedly contains the meaning of life.